Pengaruh Lingkungan Keluarga, Motivasi Instrinsik, Dan Pengetahuan Kewirausahaan Terhadap Intensi Berwirausaha Mahasiswa Fakultas Ekonomi Universitas Negeri Jakarta - Alicia Florentina; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (JURNAL RISET MANAJEMEN (JURMA), 2024)
Entrepreneurship is anything that aims to build a mindset, skills and creativity in entrepreneurship by absorbing aspects that will result in ideas and innovations. Problems that arise along with entrepreneurship in intense entrepreneurship. With this research, researchers conducted research on the intensity of entrepreneurship among students class of 2021, Faculty of Economics, Jakarta State University. This research aims to determine the influence of family environment on entrepreneurial intensity, intrinsic motivation on entrepreneurial intensity, entrepreneurial knowledge on entrepreneurial intensity, as well as family environment, intrinsic motivation, entrepreneurial knowledge together with student entrepreneurial intensity. This research uses quantitative methods. Data obtained through survey data collection methods via Google Form. The population used in this research was 367 students and a sample of 112 respondents. The data analysis technique used in this research is linear. Regression techniques consisting of validity, reliability, normality, linearity, autocorrelation, multicollinearity, heteroscedasticity, t test, F test and coefficient of determination tests were carried out using SmartPLS 4 software.